Creating conditions for sustainable degree apprenticeships in England. Issue 5 (6th July 2020) - Lester, Stan
Abstract : Purpose: The purpose of this paper is to report on a study funded by the Edge Foundation, an independent educational charity, to investigate what is needed in order for English higher education to operate degree apprenticeships (DAs) on a sustainable basis. Design/methodology/approach: The study, conducted in 2019–2020, took the form of a literature review, semi-structured interviews with employers, institutional staff members and apprentices in three fields, and an open online survey. Findings: This study illustrates a high level of support for DAs amongst those who are involved in them, whether as educators, employers or apprentices. Degree Apprenticeships aid public-sector recruitment, support progression routes and social mobility within the existing workforce, and contribute to recruitment and productivity in public services and economically critical industries. Practices in the organisation and delivery of apprenticeships are variable, but a clear need is illustrated for strong institution–employer partnerships, integration between on- and off-the-job learning, expansive workplace learning environments, and co-ordination of assessment and quality assurance. There is also a need for external bodies to provide a consistent policy and funding environment. Practical implications: The findings illustrate the need for strong partnerships, for programmes that are designed from the ground up as apprenticeships, and for effective integration of apprentices into the organisation's working environment. Originality/value: This study updates and adds to the literature on DAs and work-integrated higher education. It emphasises three aspects that have hitherto been given little attention: the value of DAs for public-sector recruitment and for creating social mobility within the existing workforce, and the importance of ensuring apprenticeships are aligned with organisational objectives.